Description of the Marottarhizoecus issisi gen. et sp. nova (Homoptera, Coccoidea, Pseudococcidae, Rhizoecinae) from Africa with a review and key of the subfamily (Bollettino di zoologia agraria e bachicoltura, 2024)
A new genus and species, Marottarhizoecus issisi gen. et sp. nova, isdescribed from Rhizoecinae subfamily.,A review and a key for genera is givenfor the subfamily.
Keywords: Homoptera; Coccoidea; Pseudococcidae; Rhizoecinae Marottarhizoecus issisi gen. and sp. nova; Africa; Tanzania; review; key